Innovative Strategies Based on Delivery Technology to Improve the Absorption and Utilization of Functional Ingredients in Sports Nutrition Foods - SONG Xinyu, LIU Xiangyu, YUE Qing, WEI Bing, SONG Guilin, ZHANG Hui, DU Pengcheng, SUN Congyu, ZHANG Ziyi, LÜ Mingchun, LI Yuan (Shipin Kexue)
Sports nutrition food is of great significance for sports persons to supplement essential nutrients timely and regulate their physical functions. Its important components include basic nutrients such as whey protein and functional ingredients such as taurine. Functional factors are crucial for enhancing athletic performance and reducing fatigue. However, they encounter challenges like poor stability, rapid degradation, and low absorption rates, which greatly restrict their health benefits. Consequently, the development of sports nutrition products featuring functional factors faces several obstacles. Delivery technologies including microcapsules, emulsions and gels have been shown to be effective in improving the stability and absorption of functional ingredients, thus having the potential to be an innovative strategy to develop functional foods. In this review, we first provide an overview of the classification and functions of sports nutrients and functional ingredients, and then introduce the mechanisms by which functional ingredients improve athletic performance. Besides, we discuss various delivery technologies suitable for sports nutrition foods and their applications and explore future directions for the sustainable development of the sports nutrition food industry. This review is expected to provide a theoretical basis and technical support for the development of highly absorbable sports nutrition food.